Determine and Control the Powdery Mildew Causal on Cucumber and Squash Plants in El-Wasta Green Mountain - Abugharsa, Issa. A.; Ehwaeti, M. K.; Younis, Y. M. (Al-Mukhtar Journal of Sciences, 2008)
The lab studies and microscopic investigation of fibrosin bodies and germ tube of infected cucumber plant with PM-disease indected that the causal of this disease was Sphaerotheca fuliginea. The treatments before and after infection were vary on both tested plants. The most effective treatment before infection on cucumber plant was top sin fungicide (5.08%), followed by mustard & garlic oil extracts (6.60 & 7.72%). While maistard oil extract reduce the disease infection percentage by 5.32% followed by garlic and topsin treatments 6.52 & 8.14% repectivelyl on squash plant after infection all the treatments were vary with control. The most active one was mustard oil on cucumber piant (7.72%) and 10.97% for top sin on squash. The juniper oil extract was the least effective in both treatments.